RFID-based smart blood stock system - Zaric, A. (2015)
A complete UHF radio-frequency identification (RFID)-based system capable of localizing individual blood bags inside storage cabinet drawers is presented. It was developed to demonstrate the improvement possibility of current blood stock management systems and as the submission to the 2014 IEEE AP-S Student Design Contest: Antennas for RFID Application. The system is composed of a cabinet model, a transceiver unit, and a PC with the controlling software. A new implementation of pseudolocalization principle is used to localize the blood bags that are equipped with dedicated passive tags designed to be resilient to blood proximity and small size. The detector antennas are placed at the drawers bottoms and additional passive tags are utilized to identify individual locations in each drawer. The transceiver unit is made from off-the-shelf commercial electronic boards and wirelessly controlled by software run on the PC. The entire system is small, transportable, battery powered, and low cost.